Interpersonal Communication Model of Prophet Muhammad SAW - Nasrullah Nasrullah; Rachmat Kriantono; Anang Sujoko (Wacana Journal of Social and Humanity Studies, 2017)
Communication models emerging and developing recently are still theoretically dominated by western perspective. â€œSeven Traditionsâ€ term previously promoted by Robert Craigh has grown into â€œTen Traditionsâ€. Other side of this prespective, eastern perspective, is indeed also meaningful in undestanding the review of communication science. Islam perspective represented by Prophet Muhammad SAW constitutes this eastern side. However, eastern perspective is not the object of spotlight in the academic review either in the west or east parts of the world. As a part of the responsibility for the intellectualism, the author feels necessary to adopt the title â€œInterpersonal Communication Model of Prophet Muhammad SAWâ€. The methodology of this review is qualitative. Literature study is used as the approach of review because the observed object is related with the history and also because field study is not reliable approach for the type of qualitative review. Result of the current review shows that communication models introduced by Prophet Muhammad SAW does not escape from the guidance and revelation of Allah SWT stated in Al Qurâ€™an and Hadist. It is expected that interpersonal communication model of Prophet Muhammad SAW should be new paradigm in the review of communication science beyond western perspective that is currently developed.